Pemetaan kualitas empirik soal ujian akhir semester pada mata pelajaran Bahasa Indonesia SMA di Kabupaten Klaten - Yulinda Erma Suryani (Graduate School, Universitas Negeri Yogyakarta, 2017)
Tujuan penelitian ini adalah untuk mengetahui kualitas empirik soal Mata Pelajaran Bahasa Indonesia yang digunakan dalam pelaksanaan ujian akhir semester SMA di Kabupaten Klaten dalam empat tahun terakhir. Jenis penelitian ini adalah deskriptif kuantitatif. Metode pengumpulan data yang digunakan dalam penelitian ini adalah dokumentasi yang mengutip respon jawaban 1125 peserta didik pada ujian akhir semester tingkat SMA di Kabupaten Klaten pada Mata Pelajaran Bahasa Indonesia kelas X pada Tahun Pelajaran 2011/2012 sampai Tahun Pelajaran 2014/2015. Analisis kualitas empirik soal ujian akhir semester meliputi: tingkat kesukaran, daya pembeda, efektivitas distraktor, validitas dan reliabilitas. Berdasarkan hasil analisis data dapat diketahui bahwa tingkat kesukaran butir soal ujian akhir semester di Kabupaten Klaten pada Tahun Pelajaran 2011/2012 kategori mudah sebanyak 64%, sedang 24 % dan sukar 12%. Pada Tahun Pelajaran 2012/2013 78% soal mudah, 12% sedang 10% sukar 10%. Pada tahun pelajaran 2013/2014 12% soal mudah, 14% sedang dan 74% sukar. Pada tahun pelajaran 2014/2015 64% mudah, 16% sedang dan 28% sukar. Daya pembeda soal ujian akhir semester pada tahun pelajaran 2011/2012 yang memenuhi kriteria sebanyak 62%, pada Tahun Pelajaran 2012/2013 sebanyak 76%, pada tahun pelajaraan 2013/2014 sebanyak 62%, pada Tahun Pelajaran 2014/2015 sebanyak 64%. Distraktor pada soal ujian akhir semester Tahun Pelajaran 2011/2012 dapat berfungsi dengan baik sebanyak 86%, pada Tahun Pelajaran 2012/2013 sebanyak 90%, pada Tahun Pelajaran 2013/2014 sebanyak 76%, pada Tahun Pelajaran 2014/2015 sebanyak 90%. Hasil analisis validitas empirik pada soal ujian akhir semester tahun pelajaran 2011/2012 diperoleh 36% butir yang valid dengan nilai koefisien reliabilitas sebesar 0,232. Pada soal ujian akhir semester tahun pelajaran 2012/2013, 56% butir soal valid dengan nilai koefisien reliabilitas 0,428. Koefisien reliabilitas soal ujian akhir semester pada tahun pelajaran 2013/2014 diperoleh sebesar 0,238 dengan butir soal yang valid 40%. Validitas empirik pada ssoal ujian akhir semester tahun pelajaran 2014/2015 sebesar 50% butir soal valid dengan nilai koefisien reliabilitas sebesar 0,603. MAPPING OF APPING OF THE EMPIRICAL QUALITY OF INDONESIAN LANGUAGE SUBJECT FINAL EXAM FOR SENIOR HIGH SCHOOL IN KLATEN REGENCYAbstractThis research aims at determining the empirical quality of Indonesian Language subject test questions used for Final Exam for senior high school in Klaten Regency within the last four years. This research uses a descriptive quantitative method. The data for this research were collected by means of documentation. Documentation that cites the responses of the students of the final exam of high school semester in Klaten Regency on the Indonesian Language Subject of class X in the 2011/2012 Year Learning Year until the 2014/2015 Lesson Year which amounts to 1125 students. Empirical quality analysis of the final exam of the semester include: item difficulty, discriminating power, distractor effectiveness, validity and reliability. Based on the results of data analysis can be seen that the level of difficulty item semester final exam in Klaten regency in the academic year 2011/2012 easy categories as much as 64%, while 24% and 12% difficult. In school year 2012/2013 78% easy problem, 12% medium 10% difficult 10%. In the academic year 2013/2014 12% easy questions, 14% medium and 74% difficult. In academic year 2014/2015 64% easy, 16% medium and 28% difficult. The discriminating power of final exam of semester in academic year 2011/2012 that have qualified as much as 62%, Lessons 2012/2013 as much as 76%, 62/2014 years of education as much as 62%, Lesson 2014/2015 as much as 64%. Distractor at the end of semester exam in the academic year 2011/2012 to function properly as much as 86%, in the Academic Year 2012/2013, as much as 90%, in the Academic Year 2013/2014 by 76%, in the Academic Year 2014/2015 by 90%. The results of empirical validity analysis on the final exam of the academic year 2011/2012 obtained 36% valid grain with the value of reliability coefficient of 0.232. On the matter of the final exam of the year 2012/2013 academic year, 56% items are valid with the value of reliability coefficient of 0.428. Reliability coefficient about final exam of semester in academic year 2013/2014 obtained equal to 0,238 with item 40% valid matter. Empirical validity in semester test case final year 2014/2015 amounted to 50% items valid with reliability coefficient value of 0.603